Parents' use of harsh punishment and young children's behaviour and achievement: a longitudinal study of Jamaican children with conduct problems. (12th October 2018) - Baker-Henningham, H.; Francis, T.
Abstract : Introduction: Harsh punishment by parents is common in low- and middle-income countries (LMIC), yet there is limited evidence from LMIC of the effects of harsh punishment on child outcomes. Methods: A longitudinal, prospective study was conducted with children with conduct problems to examine the associations between parents' use of harsh punishment during the preschool years on child behaviour and school achievement in grade one of primary school. As part of an efficacy trial in 24 preschools, 225 children with the highest level of teacher-reported conduct problems were evaluated and their parents reported on how often they used harsh punishment. Outcome measures in grade one included child conduct problems by independent observation, teacher and parent report, child social skills by teacher and parent report, direct tests of children's academic achievement and language skills, and tester ratings of child attention and impulse control. Results: Children had a mean age of 6.92 years and 61% were boys. All parents reported using harsh punishment. After controlling for child age and sex, socio-economic status, parents' involvement with child and maternal education, frequency of harsh punishment was associated with growth in child conduct problems by independent classroom observations ( p   =  0.037), parent ( p   =  0.018) and teacher ( p   =  0.044) report, a reduction in child social skills by teacher ( p   =  0.024) and parent ( p   =  0.014) report and poorer attention during the test session ( p   =  0.049). Conclusion: The associations between frequency of parents' use of harsh punishment with their preschoolers with conduct problems and later child behaviour indicate a need to train parents in non-violent behaviour management.